1997
DOI: 10.1681/asn.v8111706
|View full text |Cite
|
Sign up to set email alerts
|

A common NKCC2 mutation in Costa Rican Bartter's syndrome patients

Abstract: Bartter's syndrome involves an overlapping set of closely related renal tubular disorders that can be subdivided into at least three clinical phenotypes: (1) the hypercalciuric antenatal Bartter variant; (2) the classic Bartter variant; and (3) the hypocalciuric-hypomagnesemic Gitelman variant. Recent data demonstrate that in several phenotypically indistinguishable cohorts, antenatal Bartter's syndrome is genetically heterogeneous. In these patients, mutations in the genes encoding either the bumetanide-sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…This fact, along with finding several heterozygous carriers (for p. Ala204Thr) in individuals with ancestry originated from Mestanza (a town founded in the 11th century, localized at the South of Ciudad Real) and a dot of confluence of Cañada Real Segoviana (4) and Cañada Real Soriana Oriental (5) ( Figure 2 ), seemed to support our hypothesis. Our data are also consistent with studies establishing a strong association between specific-unique mutations and population founder effects on BS [ 7–9 ], such as in Korea and Japan [ 8 , 9 ] or Costa Rican populations [ 10 ] ( Supplementary data, Table S2 ).…”
supporting
confidence: 91%
“…This fact, along with finding several heterozygous carriers (for p. Ala204Thr) in individuals with ancestry originated from Mestanza (a town founded in the 11th century, localized at the South of Ciudad Real) and a dot of confluence of Cañada Real Segoviana (4) and Cañada Real Soriana Oriental (5) ( Figure 2 ), seemed to support our hypothesis. Our data are also consistent with studies establishing a strong association between specific-unique mutations and population founder effects on BS [ 7–9 ], such as in Korea and Japan [ 8 , 9 ] or Costa Rican populations [ 10 ] ( Supplementary data, Table S2 ).…”
supporting
confidence: 91%
“…The homozygous loss‐of‐function SLC12A1 mutation in humans is responsible for the antenatal form of Bartter syndrome type I (Kurtz et al., 1997; Nozu et al., 2009; Simon et al., 1996; Vargas‐Poussou et al., 1998). This is an autosomal recessive disorder characterized by abnormally high levels of amniotic fluid surrounding the affected fetus (polyhydramnios) that closely resembles the symptoms of hydrallantois in Japanese Black cattle.…”
Section: Resultsmentioning
confidence: 99%
“…In most of them, the pregnancy was complicated due to polyhydramnios and they were born prematurely. In the subset of patients that was later available for genetic testing, Kurtz et al 9 identified a predominant mutation on the SCL12A1 gene, which is known to be cause of BS type I. 4,6,9,10 Birkenhäger et al 11 identified 7 different mutations in the BSND gene, and there have been reported more allelic variants.…”
Section: Discussionmentioning
confidence: 99%
“…In the subset of patients that was later available for genetic testing, Kurtz et al 9 identified a predominant mutation on the SCL12A1 gene, which is known to be cause of BS type I. 4,6,9,10 Birkenhäger et al 11 identified 7 different mutations in the BSND gene, and there have been reported more allelic variants. Besides, the same mutation may originate different clinical phenotypes, because of the individual variability in the genes of additional channels or in the modifying genes that regulate the expression.…”
Section: Discussionmentioning
confidence: 99%